Work migrants negative impact on the market of labour (The Journal of Psychology and Sociology, 2012)
This article examines the processes of migration and migrant workers and the problem of its purchase of an illegal nature. The object of study of this article is illegal labour migrants, the subject is negative influence on the structure of society.As a result of research of the given problem were identified the internal and external factors of influence on the migra- tion processes, were analyzed the Agency statistics of the RK and the following conclusions were made: increasing of competition in the local labour market with the local population, monopolization by migrants of some sectors of economic activity that as a whole leads to social tensity in the region.
Keywords: migration; illegal migrants; monopoly.